Cricoid Pressure Impedes Tracheal Intubation With the Pentax-AWS Airwayscope®: A Prospective Randomized Trial. Issue 4 (August 2016) - Komasawa, N.; Kido, H.; Miyazaki, Y.; Tatsumi, S.; Minami, T.
Abstract : (Abstracted from Br J. Anaesth, 116(3):413–416, 2016) The purpose of this study was to determine how use of the Pentax-AWS AirwayScope (AWS; Hoya, Tokyo, Japan) video laryngoscope was affected by cricoid pressure (CP). Sixty anesthetized patients participated in this prospective randomized clinical trial.